Nutrition-sensitive agriculture: new term or new concept? - Balz, Angelina G.; Heil, Eleonore A.; Jordan, Irmgard; Justus Liebig University Giessen (My University, 2015)
Within the post-2015 agenda discussions of the United Nations, sustainable development goals (SDGs) are being drafted. In this context, nutrition-sensitive agriculture has been introduced. Nutrition-sensitive approaches in general are not new. They refer to improving or at least avoiding harm to the underlying and basic causes of malnutrition presented in the UNICEF conceptual framework. In order to answer the question of whether nutrition-sensitive agriculture is only a new term or also a new actionable concept with a comprehensive definition, framework, and political will, a questionnaire-based survey with representatives from 18 agricultural ministries of various countries was conducted on the basis of a literature review. Furthermore, the Final Communiqué of the Berlin Agriculture Ministers Summit 2014 was analyzed as an indication of political commitment following the steps of the qualitative content analysis of Mayring.
Keywords: nutrition-agriculture linkages; food system; agricultural policy; UNICEF model; Second International Conference on Nutrition (ICN2); ddc:610